2007
DOI: 10.1109/tbme.2007.891169
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Carbon Nanofiber Architecture as a Multifunctional 3-D Neural Electrical Interface

Abstract: Developing biomaterial constructs that closely mimic the natural tissue microenvironment with its complex chemical and physical cues is essential for improving the function and reliability of implantable devices, especially those that require direct neural-electrical interfaces. Here we demonstrate that free-standing vertically aligned carbon nanofiber (VACNF) arrays can be used as a multifunctional 3-D brush-like nanoengineered matrix that interpenetrates the neuronal network of PC12 cells. We found that PC12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(92 citation statements)
references
References 38 publications
4
87
0
1
Order By: Relevance
“…Schematic representation of experimental approach. scaffold [9,22]. For instance, Cho and Borgens prepared electrically conductive collagen/MWCNT composite structures and investigated the effect of CNT loading and applied electrical stimuli on the cell viability of PC12 [29].…”
Section: Seeding Mscs On the Patterned Cnt Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Schematic representation of experimental approach. scaffold [9,22]. For instance, Cho and Borgens prepared electrically conductive collagen/MWCNT composite structures and investigated the effect of CNT loading and applied electrical stimuli on the cell viability of PC12 [29].…”
Section: Seeding Mscs On the Patterned Cnt Arraysmentioning
confidence: 99%
“…Recently, numerous studies reported on the effects of topographical patterns on cell viability [6,7]. In this regard, patterning of scaffold surfaces at a nanometer scale is considered as a promising tool [8,9]. It is reported that gene expressions of fibroblast cells were found to be enhanced on relatively rougher surfaces [10].…”
Section: Introductionmentioning
confidence: 99%
“…This assumption is made upon numerous research efforts to grow neurons on substrates (e.g., [15]) and design topologically-specific neuronal networks (e.g., [9,13,21]). Figure 3 illustrates an example neuron-based BANN.…”
Section: Neuron-based Body Area Nanonet-work (Banns)mentioning
confidence: 99%
“…18 -20 In addition, the development of carbon nanotube technologies appear to have potential to help to establish biologically advantageous connections to neurons with improved electrical properties. 21 Other areas of improvement include the incorporation of microfluidics into silicon-based devices. Currently, there are few options for stable, long-term recording arrays that can meet the required biocompatibility standards for materials implanted into the brain (e.g., use of platinum/ iridium electrode coatings), severely limiting even highly preliminary testing of these devices for human use.…”
Section: Signal Detectionmentioning
confidence: 99%